Self‐Efficacy of Counselors Working With Refugees. Issue 2 (11th October 2020) - Isawi, Dana T.; Post, Phyllis B.
Abstract : Counselors have the ethical responsibility to meet the mental health needs of refugees who are forced to leave their home countries. This study examined factors influencing the self‐efficacy of counselors (N = 98) working with refugees. The results revealed a relationship between trauma training and secondary traumatic stress and counselor self‐efficacy. Implications for clinical practice and research are discussed.